Ulama dan Perubahan Sosial dalam Islam - Hj. Ab Majid, Mohamad Kamil (Jurnal Usuluddin, 1999)
This article describes the defination of ulama and their roles in social change which can be seen clearly in both fields; education and leadership. It also discusses about a deep relationship between the institution of ulama and the Muslims political order.